THE USE OF SMALL GROUP DISCUSSION IN IMPROVING STUDENTS’ READING COMPREHENSION (A STUDY CONDUCTED AT SMP NEGERI 1 LANGOWAN) - Stella S Tambuwun; Deysi Batunan; Tirza Kumayas (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
The purpose of this research is to found out whether or not small group discussion could improve students’ reading comprehension through pre experimental design with one group pre-test and post-test design as quantitative research. The data collection in this research consists of 10 essay questions with 2 points for each question and 20 points for total point of the questions. The subject of this research was the eighth students in SMP N 1 Langowan which consisted of 20 students. This research is conducted during pandemic of Covid-19 so it is held online with using social media and video call to ensure students and teacher health following the health protocol to minimalized physical interaction and to make sure parents and students feel save in their house but still maintained to make sure students were focus in their online class meeting. The data of this research are analysed statistically using mean score formula. The result in this study shows that the score of the post-test is higher than the result of the pre-test. The mean score of the pre-test is 42,5 and in post-test is 77,5. It could be concluded that Small Group Discussion is effective to improve students’ reading comprehension on narrative text.